DNA Aptamer Raised Against Advanced Glycation End Products (AGEs) Improves Glycemic Control and Decreases Adipocyte Size in Fructose-Fed Rats by Suppressing AGE-RAGE Axis - Ojima, A.; Matsui, T.; Nakamura, N.; Higashimoto, Y.; Ueda, S.; Fukami, K.; Okuda, S.; Yamagishi, S. (Hormone and Metabolic Research, 2015)
Advanced glycation end products (AGEs) decrease adiponectin expression and suppress insulin signaling in cultured adipocytes through the interaction with a receptor for AGEs (RAGE) via oxidative stress generation. We have recently found that high-affinity DNA aptamer directed against AGE (AGE-aptamer) prevents the progression of experimental diabetic nephropathy by blocking the harmful actions of AGEs in the kidney. This study examined the effects of AGE-aptamer on adipocyte remodeling, AGE-RAGE-oxidative stress axis, and adiponectin expression in fructose-fed rats. Although AGE-aptamer treatment by an osmotic mini pump for 8 weeks did not affect serum insulin levels, it significantly decreased average fasting blood glucose and had a tendency to inhibit body weight gain in fructose-fed rats. Furthermore, AGE-aptamer significantly suppressed the increase in adipocyte size and prevented the elevation in AGEs, RAGE, and an oxidative stress marker, 8-hydroxydeoxyguanosine (8-OHdG), levels in adipose tissues of fructose-fed rats at 14-week-old, while it restored the decrease in adiponectin mRNA levels. Our present study suggests that AGE-aptamer could improve glycemic control and prevent adipocyte remodeling in fructose-fed rats partly by suppressing the AGE-RAGE-mediated oxidative stress generation. AGE-aptamer might be a novel therapeutic strategy for fructose-induced metabolic derangements.
Keywords: AGEs; RAGE; oxidative stress; adiponectin; adipocytes; aptamer